Financial risk-taking and the gender wage gap - Per-Anders Edin; Håkan Selin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
Could differences in risk attitudes explain parts of the gender wage gap? We present estimates on the association between labor market outcomes and financial risk-taking using individual level administrative data on individual wealth portfolios and wage rates. The individual's share of risky to total financial assets i s significantly and positively associated with the wage rate. However, it turns out that our risk measure explains only a small part of the observed gender difference in wages.
Keywords: J31; D8; 330; Wages; human capital; financial risk